Optimalisasi Pemanfaatan Media Sosial dalam Promosi Kampung Wisata Pekijing - Nana Sutisna Amdan; Muhammad Ihsan Alifi; Muhaemin Muhaemin; Aditya Ramadhan; Maulia Pratiwi; Neka Fitriyah; Ail Muldi (Universitas Mathla'ul Anwar Banten, 2022)
The success of marketing a product, one of which depends on the ability of producers to promote their products. Promotion is an activity that is very commonly done by marketers to provide information related to products and encourage potential consumers to buy goods or services offered. Pekijing Village, Kalang Anyar Village, Taktakan District, Serang City, Banten Province, which has been renovated into a tourist village, is still not widely known to the public. Promotions carried out by local residents have not had much impact in increasing tourist visits. The service team seeks to provide solutions by providing training on the use of social media, namely YouTube, Instagram, Facebook and TikTok, as a means of promotion. The training was given to 30 local youths, for 1 month, with the aim of providing knowledge and practice as well as assisting residents in marketing their village as a tourist destination. The stages of service are planning, implementation, follow-up and evaluation. As a result of this service activity, the 30 youths received sufficient information and knowledge regarding the characteristics of social media, content production techniques, content title and strategies for using social media. After a month of being given training and guidance, 18 of the 30 youths who were given training began to optimize the use of social media as a means of promoting the potential of their village.